Dynamic changes of soil microorganisms in rotation farmland at the western foot of the Greater Khingan range - Wei, Shuli; Fang, Jing; Zhang, Tianjiao; Wang, Jianguo; Cheng, Yuchen; Ma, Jie; Xie, Rui; Liu, Zhixiong; Su, Erhu; Ren, Yongfeng; Zhao, Xiaoqing; Zhang, Xiangqian; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Crop rotation and other tillage systems can affect soil microbial communities and functions. Few studies have reported the response of soil spatial microbial communities to rotation under drought stress. Therefore, the purpose of our study was to explore the dynamic changes of the soil space microbial community under different drought stress-rotation patterns. In this study, two water treatments were set up, control W1 (mass water content 25%-28%), and drought W2 (mass water content 9%-12%). Four crop rotation patterns were set in each water content, spring wheat continuous (R1), spring wheat-potato (R2), spring wheat-potato-rape (R3) and spring wheat-rape (R4), for a total of eight treatments (